Quality of care for elderly residents in nursing homes and elderly people living at home: controlled observational study - Fahey, Tom (BMJ Publishing Group Ltd, 2003)
OBJECTIVES: To assess the quality of care given to elderly people and compare the care given to residents in nursing homes with those living in their own homes. DESIGN: Controlled observational study. SETTING: Primary care, Bristol. SUBJECTS: Elderly individuals (aged ⩾65 years) registered with three general practices, of whom 172 were residents in nursing homes (cases) and 526 lived at home (matched controls). MAIN OUTCOME MEASURES: The quality of clinical care given to patients was measured against explicit standards. Quality indicators were derived from national sources and agreed with participating general practitioners. RESULTS: The overall standard of care was inadequate when judged against the quality indicators, irrespective of where patients lived. The overall prescribing of beneficial drugs for some conditions was deficient—for example, only 38% (11/29) (95% confidence interval 20% to 58%) of patients were prescribed β blockers after myocardial infarction. The proportion of patients with heart disease or diabetes who had had their blood pressure measured in the past two years (heart disease) or past year (diabetes) was lower among those living in nursing homes: for heart disease, 74% (17/23) v 96% (122/127) (adjusted odds ratio 0.18, 0.04 to 0.75); for diabetes, 62% (8/13) v 96% (50/52) (adjusted odds ratio 0.05, 0.01 to 0.38). In terms of potentially harmful prescribing, significantly more patients in nursing homes were prescribed neuroleptic medication (28% (49/172) v 11% (56/526) (3.82, 2.37 to 6.17)) and laxatives (39% (67/172) v 16% (85/526) (2.79, 1.79 to 4.36)). Nursing home residents were less likely to have the appropriate diagnostic Read code linked to their prescribed neuroleptic drug (0.22, 0.07 to 0.71). CONCLUSIONS: The quality of medical care that elderly patients receive in one UK city, particularly those in nursing homes, is inadequate. We suggest that better coordinated care for these patients would avoid the problems of overuse of unnecessary or harmful drugs, underuse of beneficial drugs, and poor monitoring of chronic disease.